Mono(2, 2′‐bipyridyl)RuII Complex with Four Dimethyl Sulfoxide Ligands as Precursor for cis‐Bis‐heteroleptic RuII Complex: Syntheses, Structures, and Substitution Reactions. Issue 39 (4th October 2018) - Toyama, Mari; Fujimoto, Daichi; Matsuoka, Yumi; Asano, Yuki; Nagao, Noriharu
Abstract : The dication complex trans (O, S)‐[Ru(bpy)(dmso‐ O )2 (dmso‐ S )2 ](OTf)2 [1· (OTf)2 ; bpy = 2, 2′‐bipyridyl; dmso = dimethyl sulfoxide; OTf – = CF3 SO3 – ] was obtained from the reaction of cis (Cl), cis ( S )‐[RuCl2 (bpy)(dmso‐ S )2 ] with Ag(OTf) in DMSO. The crystal structure of1· (OTf)2 revealed two labile dmso‐ O ligands and two less‐labile dmso‐ S ligands positioned cis to each other. In DMSO, the equatorial dmso‐ O in1 2+ equilibrates with its linkage isomer dmso‐ S to fac ( S )‐[Ru(bpy)(dmso‐ O )(dmso‐ S )3 ] 2+ [1iso 2+ ] ([1iso 2+ ]/[1 2+ ] = 3:97 at 298 K and 33:67 at 373 K). The linkage isomerization kinetic parameters, deter min ed by 1 H NMR, were Δ H = 22(1) kJ mol –1 and Δ S = 52(2) J mol –1 K –1 . The two O ‐bonded dmso ligands of1· (OTf)2 were easily solvolyzed in MeCN to form trans (NMeCN, S)‐[Ru(bpy)(MeCN)2 (dmso‐ S )2 ](OTf)2 [2· (OTf)2 ]. Moreover, the reaction of1· (OTf)2 with 1, 10‐phenanthroline (phen) in acetone afforded cis ‐[Ru(bpy)(phen)(dmso‐ S )2 ](OTf)2 [3· (OTf)2 ] in very good yield (95 %) and excellent purity. Abstract : 1· (OTf)2 was efficiently synthesized. In DMSO, the equatorial dmso‐ O reversibly isomerizes into the S ‐bonded form, 1iso · (OTf)2 . In MeCN, both O ‐bonded dmso ligands in1 2+ are selectively replaced to form2· (OTf)2 . Finally, the reaction of1· (OTf)2 with phen in acetone affords the cis ‐bis‐heteroleptic complex3· (OTf)2 in good yield.